Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/1462-2920.14083
|View full text |Cite
|
Sign up to set email alerts
|

2‐Tridecanone impacts surface‐associated bacterial behaviours and hinders plant–bacteria interactions

Abstract: Surface motility and biofilm formation are behaviours which enable bacteria to infect their hosts and are controlled by different chemical signals. In the plant symbiotic alpha-proteobacterium Sinorhizobium meliloti, the lack of long-chain fatty acyl-coenzyme A synthetase activity (FadD) leads to increased surface motility, defects in biofilm development and impaired root colonization. In this study, analyses of lipid extracts and volatiles revealed that a fadD mutant accumulates 2-tridecanone (2-TDC), a methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…The 2-methylketones, primarily 2-undecanone and 2-tridecanone, from wild tomatoes act as natural insecticides [11]. Although the biological function of ShMKS2 homologs in other plant species remains to be elucidated, there is cumulative evidence that suggests a defensive role for MKS2/ALT-like proteins in those plants [10,17,19,29]. In eggplants, artificial wounding, methyl jasmonate (MeJA) treatment, or methyl salicylate (MeSA) treatment upregulated the transcriptional expression of SmMKS2-1 gene in the leaves [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 2-methylketones, primarily 2-undecanone and 2-tridecanone, from wild tomatoes act as natural insecticides [11]. Although the biological function of ShMKS2 homologs in other plant species remains to be elucidated, there is cumulative evidence that suggests a defensive role for MKS2/ALT-like proteins in those plants [10,17,19,29]. In eggplants, artificial wounding, methyl jasmonate (MeJA) treatment, or methyl salicylate (MeSA) treatment upregulated the transcriptional expression of SmMKS2-1 gene in the leaves [29].…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, herbivore-damaged plants emitted more 2-pentanone than undamaged plants [36]. In addition to the protective role against herbivorous insects, 2-tridecanone can also affect surface mobility and biofilm formation of both pathogenic and symbiotic bacteria and as a result, interfere with the bacterial colonization of plant roots [19]. In this study, we also observed that the main transcript of GmMKS2 , GmMKS2-X2 , was universally present in all tissues examined, but its expression was the highest in the roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rhizobia, QS usually relies on the production and perception of N-acyl-homoserine lactones (AHLs) that control important functions, some of which are relevant for the interaction with the legume host (Calatrava-Morales et al, 2018). Strigolactones (SLs), a group of carotenoid-derived plant hormones exuded by roots, participate in the interaction of plants with beneficial soil microorganisms (López-Ráez et al, 2017).…”
Section: Rhizobium-legume Symbosis: Complex Signal Exchange In the Rhizospherementioning
confidence: 99%
“…However, the accumulation of free fatty acids was not responsible for the swarming phenotype observed in a S. meliloti fadD-mutant. Instead, the fadD-associated swarming phenotype was due to increased formation of the volatile 2-tridecanone [4].…”
Section: Introductionmentioning
confidence: 96%